Queue-Aware Finite-Blocklength Coding for Ultra-Reliable and Low-Latency Communications: A Cross-Layer Approach - Zhao, Xiaoyu; Chen, Wei; Poor, H. Vincent (IEEE transactions on wireless communications, 2022)
To provide reliable transmissions with low-latency requirements, we focus on Finite-Blocklength Coding (FBC) in Ultra-Reliable and Low-Latency Communications (URLLC). However, ensuring the reliability and latency of FBC has remained an open issue in URLLC. In this paper, we develop a queue-aware FBC scheme under random arrivals. With the awareness of queue length, we employ variable-length coding to jointly encode packets, through which we obtain a benefit on reliability. Meanwhile, we optimize latency under a cross-layer approach, in which two classes of variable-length codes are investigated with resources allocated in the frequency and time domains, respectively. To obtain an optimal reliability-latency tradeoff under variable-length FBC, we first present the reliability and latency performance for single links based on a Constrained Markov Decision Process (CMDP). Providing reliability with a power allocation, we then obtain the optimal tradeoff by a Linear Programming (LP) problem, in which the probability of violation of the constraints on queue length and the number of transmitted packets is minimized under average constraints on resources. Moreover, we show an optimal threshold-based policy under Bernoulli arrivals. We finally consider some extensions of the optimal tradeoff for multi-user downlinks as well as single links with retransmission.